ARCHAEOLOGICAL INVESTIGATIONS AT GOSTYNNYI DVIR (City: History, Culture, Society, 2020)
Podil standing expedition conducted the rescue excavations at Kontraktova square, Kyiv Podil in 2013. The inner part of Hostynnyj Dvir was excavated. Numerous materials are included in databases that are focused on functions of the Market square in Kyiv Rus time. This book is dedicated to the 30-years anniversary of the Podil standing archaeological expedition that was founded on 24.07.1984.The excavated part of the Market square was located within the inner space of the construction. Differences in elevations are ranged between 103.25 and 103.65 (Baltic scale). The area of 506 square meters was investigated.Archaeological work reached a depth of 3.60 meters from the recent surface. Excavations in 2013 led to the identification of the city life from Kyiv Rus time to 19th century. The remains of market rows of the 18–19th century and two layers of the 12–13th century were excavated. The obtained materials allow the reconstruction of life in Podil at a different time.Most of the researchers of Kyiv locate the main market and public centre of Kyiv, Torgovishche and city «viche» place near Hostynnyi Dvir. However, the Podil market square, which is mentioned in written sources, was not localized archaeologically. Most probably, the Uspinnia Presviatoi Bohorodytsi Pyrohoshchi church was its centre (1132–1136). Therefore, excavations of the Kyiv Rus cultural layers were extremely important in terms of localization of the Torhovyshche.Elements of Kyiv Rus constructions are fragmentary in the result of the relatively small size of the excavation site. Ditches – remains of the fences and post-holes were identified. Ceramics is dated by 11–13th century. Also, two households of the 12th century, bordered by the fences, were found. The place between these fences, 2.40 meters wide is interpreted as the remains of an alley.Identification of the fences could mark the household type of the constructions here. They could mark the eastern border of Torhovyshche. Maybe, the mentioned alley was connected to the Market square. Remains of the metallurgical production confirm the existence of the production centre in the household dated by 12–13 century. If Pyrohoshcha is taken for the center, reconstruction of the Market square is possible. However,additional excavations are still required.Cultural layers of the 14–17th century at this territory were not identified, but ceramics of this time was found. Probably, dwellings were not constructed hereafter the Mongols invasion. It is not excluded that Market square was traditionally located at the same place in post-Mongol and Late Medieval time. In the 15th century Kyiv obtained the “Magdeburger Recht”, and Torhovishce was re-named to Market Square. The wooden city hall was constructed here. In 18th century market rows were located at this place. They were replaced by the stone Hostynnyi Dvir in the 19th century.Layers of the 18th century contained numerous data. Remains of the wooden constructions (market rows) of the second half of the 18th century were identified across the area of the excavation site. Typical features of the construction of dwellings that were related to Hostynnyi Dvir correspond to the drawings of A. Melensky. Ceramics of the 17–18th century, Russian (43) and Polish (3) coins dated by 1638–1760es were found. Late Medieval objects represent a single complex that allows the reconstruction of the wooden market rows.It should be noted that this book is the first monograph in the archaeology of Kyiv that deals with the rescue excavations. Besides archaeological data, it includes the results of special analyses of the medieval ceramics and glass, amphorae, paleobotanic remains, the numismatic collection that represents the city life in Kyiv in different time periods.